Hannah Arendt and the promises of politics beyond sovereignty - João Batista Farias Junior (Argumentos, 2021)
Hannah Arendt expresses several critiques of the Western philosophical tradition in her work due to conceptual misunderstandings that played a crucial role in the course of many events in our history. This article attempts to understand how concepts such as power, freedom, and sovereignty appear in Arendt's thinking and shed light on our understanding of politics. Thinking about the relationship between these elements allows us to understand that there are other possibilities for politics besides representative democracies. It is about seeking the centrality of politics as an exercise of freedom that is only possible when we meet and act in concert.